Intravesical High Dose BCG Tokyo and Low Dose BCG Tokyo with GMCSF+IFN α Induce Systemic Immunity in a Murine Orthotopic Bladder Cancer Model - Sin Mun Tham; Juwita N. Rahmat; Edmund Chiong; Qinghui Wu; Kesavan Esuvaranathan; Ratha Mahendran (Biomedicines, 2021)
This study evaluates a short therapy schedule for bladder cancer using BCG Tokyo. BCG Tokyo was evaluated in vitro using bone marrow derived dendritic cells, neutrophils, RAW macrophages and the murine bladder cancer cell line, MB49PSA, and compared to other BCG strains. BCG Tokyo > BCG TICE at inducing cytokine production. In vivo, high dose (1 × 107 colony forming units (cfu)) and low dose (1 × 106 cfu) BCG Tokyo with and without cytokine genes (GMCSF + IFNα) were evaluated in C57BL/6J mice (n = 12–16 per group) with orthotopically implanted MB49PSA cells. Mice were treated with four instillations of cytokine gene therapy and BCG therapy. Both high dose BCG alone and low dose BCG combined with cytokine gene therapy were similarly effective. In the second part the responsive groups, mice (n = 27) were monitored by urinary PSA analysis for a further 7 weeks after therapy cessation. More mice were cured at day 84 than at day 42 confirming activation of the immune system. Cured mice resisted the re-challenge with subcutaneous tumors unlike naïve, age matched mice. Antigen specific T cells recognizing BCG, HY and PSA were identified. Thus, fewer intravesical instillations, with high dose BCG Tokyo or low dose BCG Tokyo with GMCSF + IFNα gene therapy, can induce effective systemic immunity.